2017
DOI: 10.1038/npp.2017.100
|View full text |Cite
|
Sign up to set email alerts
|

Entorhinal Cortical Deep Brain Stimulation Rescues Memory Deficits in Both Young and Old Mice Genetically Engineered to Model Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive cognitive decline. Deep brain stimulation (DBS) has been used to treat a variety of brain disorders and shows promise in alleviating cognitive symptoms in some AD patients (Laxton et al, 2010). We previously showed that DBS of the entorhinal cortex (EC) enhances spatial memory formation in normal (wild-type) mice (Stone et al, 2011). Here we tested the effects of EC-DBS on the progressive cognitive deficits in a genetically-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 43 publications
(46 reference statements)
6
52
0
Order By: Relevance
“…Interestingly, despite the loss of CA1 neurons in GI-DBS ON rats, we found that they not only performed significantly better than GI-DBS OFF rats during a probing test, but memory performance was rescued to a level similar to those of NS control groups (Fig. 3B).These results are consistent with our previous findings showing that DBS improves memory performance in wild-type animals and animals with Alzheimer's-like pathology Xia et al, 2017;Mann et al, 2018). Indeed, 6 weeks after receiving 1 h of EC DBS, naive C57BL/6 mice exhibited significant improvement in MWM performance compared with nonstimulated mice (Stone Figure 5.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, despite the loss of CA1 neurons in GI-DBS ON rats, we found that they not only performed significantly better than GI-DBS OFF rats during a probing test, but memory performance was rescued to a level similar to those of NS control groups (Fig. 3B).These results are consistent with our previous findings showing that DBS improves memory performance in wild-type animals and animals with Alzheimer's-like pathology Xia et al, 2017;Mann et al, 2018). Indeed, 6 weeks after receiving 1 h of EC DBS, naive C57BL/6 mice exhibited significant improvement in MWM performance compared with nonstimulated mice (Stone Figure 5.…”
Section: Discussionsupporting
confidence: 91%
“…The beneficial results of DBS on memory shown here are complemented by observations in other models of neurological disorders. We have previously shown that acute (1 h) and chronic EC DBS can restore memory functions in different mouse models of AD (Xia et al, 2017;Mann et al, 2018). These robust findings in AD mice support the promising effects of DBS in AD patients regarding cognitive function, disease progression, and increased cortical glucose metabolism (Laxton et al, 2010;Sankar et al, 2015).…”
Section: Discussionsupporting
confidence: 55%
“…We identified that latestage CLN3 -/mice, like several mouse models of AD, have a decrease in the absolute number of hippocampal SWRs, a physiologic oscillation important for memory consolidation (31)(32)(33). Identification of shared network features could motivate future studies of network-targeted therapies, which are under development for AD (45)(46)(47)(48), in CLN3 disease. Studies of hippocampal-mediated learning and memory in CLN3 -/mice across the life span are needed to fully characterize the impact of these network alterations.…”
Section: Discussionmentioning
confidence: 97%
“…Although the nature of how DBS works is rather complex, the overarching principle is to modulate the firing of neurons in highly specific brain regions with high temporal resolution through electrical stimulation, which makes it a prime technique for altering memory systems. Much research has focussed on applying DBS to alter memory as possible treatments for learning and memory-related disorders such as Alzheimer's disease and other dementias [4][5][6][7], anxiety-related disorders [8][9][10][11][12][13], and addiction disorders [14][15][16]. However, the application of DBS has created an interesting paradox in which the mode of treatments for dementias and treatments for anxiety or addiction appear to oppose each other.…”
mentioning
confidence: 99%